Academic Procrastination and Smartphone Addiction: A Dual “Inhibition–Substitution” Pathway and a Contextual Framework of “Rhythm–Restraint–Support” (Journal of research in medical and health sciences, 2025)
In today’s mobile, high-temptation environment, academic procrastination and smartphone addiction among university students are not isolated phenomena; rather, they co-evolve under the tension between immediate rewards and delayed returns. On the basis of clarifying conceptual boundaries—defining smartphone addiction as the co-occurrence of loss of control, excessive use, and functional impairment, and defining academic procrastination as non-necessary delay accompanied by negative affect—this paper proposes an integrative framework centered on self-control. First, self-control operates via an inhibition pathway that reduces passive distractions and in-the-moment unlocking, and a substitution pathway that offers low-cost strategies for emotion and attention regulation, thereby interrupting the cycle of “anxiety → scrolling → greater anxiety.” Second, behavior emerges from the joint shaping of motivation–incentive–context: weak intrinsic motivation amplifies the substitutive pull of the phone; algorithmic recommendation increases temptation density; and loose learning structures raise the cost of self-regulation. Third, the paper advances context-sensitive interventions and actionable scaffolds under a “rhythm–restraint–support” framework—using implementation intentions and proximal, specific sub-goals to translate long-term aims into executable schedules, and employing fixed deep-work blocks, minimal device accessibility, and process-oriented assessment to lower choice costs and create positive feedback. The contribution lies in translating self-control from an abstract “willpower” notion into a designable and assessable system of action, offering practicable pathways for university curricula and learning support, and laying out structured propositions and operational indicators for subsequent quantitative testing and contextualized practice.
Keywords: academic procrastination; smartphone addiction; self-control; process-oriented (formative) assessment; compensatory use